Investigation of Ultradispersed Powders Fe[x]O[y] Obtained in the Electric Discharge Plasma; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Lomakina A. A.; Shanenkov I. I. Ivan Igorevich (Material Engineering and Technologies, 2015)
Title screen